Member states of the European Union / edited by Simon Bulmer and Christian Lequesne. - Bulmer, Simon, 1954-; Lequesne, Christian (The new European Union series, 2005)
This is a comprehensive and rounded thematic study of the EU-member states. The text provides detailed coverage of the principal member states and comparative studies of the smaller states, as well as discussing the issue of enlargement and covering empirical themes.